Upregulation of Mcl-1S Causes Cell-Cycle Perturbations and DNA Damage Accumulation - Streletskaia, Alena Y.; Senichkin, Viacheslav V.; Prikazchikova, Tatiana A.; Zatsepin, Timofei S.; Zhivotovsky, Boris; Kopeina, Gelina S. (Frontiers in Cell and Developmental Biology, 2020)
As an important regulator of apoptosis, Mcl-1 protein, a member of the Bcl-2 family, represents an attractive target for cancer treatment. The recent development of novel small molecule compounds has allowed Mcl-1-inhibitory therapy to proceed to clinical trials in cancer treatment. However, the possible adverse effects of either direct inhibition of Mcl-1 or upregulation of Mcl-1S, proapoptotic isoform resulting from alternative splicing of Mcl-1, remain unclear. Here, we investigated changes in Mcl-1S levels during cell cycle and the cell cycle-related functions of Mcl-1 isoforms to address the above-mentioned concerns. It was shown that an anti-mitotic agent monastrol caused accumulation of Mcl-1S mRNA, although without increasing the protein level. In contrast, both mRNA and protein levels of Mcl-1S accrued during the premitotic stages of the normal cell cycle progression. Importantly, Mcl-1S was observed in the nuclear compartment and an overexpression of Mcl-1S, as well as knockdown of Mcl-1, accelerated the progression of cells into mitosis and resulted in DNA damage accumulation. Surprisingly, a small molecule inhibitor of Mcl-1, BH3-mimetic S63845, did not affect the cell cycle progression or the amount of DNA damage. In general, upregulated Mcl-1S protein or genetically inhibited Mcl-1L were associated with the cell cycle perturbations and DNA damage accumulation in normal and cancer cells. At the same time, BH3-mimetic to Mcl-1 did not affect the cell cycle progression, suggesting that direct inhibition of Mcl-1 is devoid of cell-cycle related undesired effects.